Desa Pancasila: The Implementation of Gotong Royong Values as Social Capital in Indonesia - Sumarmi, Sumarmi; Untari, Sri; Meiji, Nanda Harda Pratama (Universitas Negeri Semarang, 2022)
Desa Pancasila is one the models to mainstream Pancasila as the national value of Indonesia. The research aimed to describe and analyze Desa Pancasila as a strategy to implement Pancasila at village level. The research design used a qualitative descriptive and literature review. Data were collected through observation, interviews, documentation, and literature review. The results showed that the community’s potential with the diversity of natural resources, human resources and cultural resources could support the implementation of Pancasila national values. Local actors (local government, community leaders, and youth groups) have a significant role in implementing national values. The collaboration of local actors is in-depth dialogue, sharing vision, building trust, building commitment, and sharing knowledge. The obstacles occurred because of the globalization process and the lack of community participation. We argue that three possible solutions to overcome these problems: (1) to put the community leaders as facilitators to implement the national values; (2) to build awareness of the communities about the nation and state through joint movements to build national insight; and (3) to make a regular interactive dialogue between local leaders and the community related to the implementation of national values.